Role of Professional Societies in the Evolution of National Policies and their Implementation:Experience of the ISTE - George, P. J. (Journal of Engineering Education Transformations, 1992)
The world of today belongs to progessionals and specialists. They have undergone systematic training which is necessary to solve a class of problems. These problems and problem-situations are integral parts of our society and of our developmental process. Solutions to such problems are to be obtained from professionals in the field.